2012
DOI: 10.1371/journal.pone.0042429
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and the Processing of Emotional Facial Expressions (EFEs): Systematic Review, Unanswered Questions and Further Perspectives

Abstract: Alexithymia is characterized by difficulties in identifying, differentiating and describing feelings. A high prevalence of alexithymia has often been observed in clinical disorders characterized by low social functioning. This review aims to assess the association between alexithymia and the ability to decode emotional facial expressions (EFEs) within clinical and healthy populations. More precisely, this review has four main objectives: (1) to assess if alexithymia is a better predictor of the ability to deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
218
6
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(279 citation statements)
references
References 149 publications
(215 reference statements)
34
218
6
8
Order By: Relevance
“…Based on these findings, Grynberg et al (2012) concluded that HAIs have problems labeling facial expressions, as they cannot process the perceptual information in a very short time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these findings, Grynberg et al (2012) concluded that HAIs have problems labeling facial expressions, as they cannot process the perceptual information in a very short time.…”
Section: Discussionmentioning
confidence: 99%
“…These deficits have been found with tasks in which participants were required to reply in a very short period of time (Pedrosa et al, 2009), as well as in those with masked stimuli to make it difficult to recognize them (Kugel et al, 2008;Reker et al, 2010), and with static emotional stimuli, such as FACS, and dynamic videos (KĂ€tsyri, Saalasti, Tiippana, von Wendt, & Sams, 2008;Ridout, Thomas, & Wallis, 2010) (for a review, see Grynberg et al, 2012).…”
mentioning
confidence: 99%
“…Interestingly, in individuals with ASD it has been shown that the impairments with the recognition of emotional facial expression may be attributed to comorbid alexithymia rather than to the clinical condition of the individual (Grynberg et al 2012). Alexithymia has also been shown to play an important role in other (but not all) emotional difficulties in individuals with ASD such as empathy (Bird et al 2010) and eye-fixation (Bird et al 2011).…”
Section: Emotional Response Incoherence In Asd and The Role Of Alexitmentioning
confidence: 99%
“…On the cognitive and affective level, alexithymia is associated with decreased empathy [10], problems in emotional processing [11] and emotional face recognition [12]. It is also associated with social anhedonia [13,14], interpersonal problems [15], and lower levels of satisfaction in intimate relationships [16].…”
Section: Introductionmentioning
confidence: 99%